Presence of iron sulfides in gray foundries manufactured in cubicle furnaces - Guerrero R. (2019)
The purpose of this work is to verify the presence of iron sulfides in gray laminar castings manufactured in a cubicle furnace using high sulfur anthracite as fuel, and to evaluate their impact on mechanical properties.In this work, 04 samples of foundries, 03 of high sulphur -above the standard for these materials- and one of low sulphur have been evaluated. The microstructural examination and analysis by scanning electron microscopy and EDAX microprobe, indicated abundant presence of inclusions of manganese sulphides, associated with these, iron sulphides and mixed of iron and manganese, especially in high sulphur samples. The evaluation of the manganese content in the samples explains the presence of iron sulfides, since according to the calculations made, it is present in the alloy even in that sample whose in a lower percentage than that required to neutralize all the S content is within the range indicated by the standards for laminar gray foundries. In addition, micropores and microchips were observed in proportions and sizes higher than those usual for pieces of standardized quality, which explains the poor mechanical behavior observed in most cases. The characteristics of the scrap used to manufacture these foundries suggest that fuel is the main source of sulfur in the samples analyzed. © 2019 IEEE.